Input-state feedback linearization for stable radio-frequency magnetron control - Victor Etxebarria; Joaquin Portilla; Jorge Feuchtwanger (Systems Science & Control Engineering)
In this study, we propose a nonlinear control method to stabilize the oscillation of magnetrons. These power microwave devices have a complex dynamics, which can be modelled as simple third-order nonlinear oscillator. This circuit can be controlled using input-state feedback linearization, and the exponential stabilization of this scheme is proved. Simulations show that the open-loop model displays common properties observed in industrial magnetrons, such as noise and chaotic behavior, which can be removed and stabilized using the proposed method. The experimental results show that the control signal injected into the magnetron resonant cavities improves its performance, as suggested.